PID Controllers Performance On Dual Axis Tracking With Tetrahedron Based Sensor - Melinda; Andri Novandri; Yuwaldi Away (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
This study compares control systems applied to a dual-axis tetrahedron-based sensor tracker. A tetrahedron-based sensor is a tracking sensor that can detect the coordinates of a light source. This study aims to determine a control system that can control sensors with high accuracy and precision and has a fast-tracking ability. Tests are carried out periodically by providing light at certain coordinates. After carrying out the testing and analysis process, it is concluded that the P controller is a better control system than the other controllers. This controller can control sensors with high accuracy and precision compared to PI, PD, and PID control systems. The P controller can also control the sensor to move towards the light coordinates with a travel time of 1.6 seconds on the X-axis and 3.1 seconds on the Y-axis, with a MAE value of 1.1 on the X-axis and 0.3 on the Y-axis. While the RSME value obtained is 1.33 on the X-axis and 0.55 on the Y-axis.